Características clínicas de trabajo de parto y su relación Con el sufrimiento fetal agudo en madres atendidas en el Hospital II-2 Minsa Tarapoto. Periodo Junio-Setiembre 2014 - Arévalo Rioja, Lucía (2014)
This research is a descriptive correlational, cross-sectional, conducted in order to determine the relationship between the clinical characteristics of labor and fetal distress in mothers treated at the Hospital II-2 MINSA Tarapoto. Period June-September 2014. The study population consisted of 40 mothers whose births concomitant with acute fetal distress that were treated at the Hospital II-2 MINSA Tarapoto from June to September 2014 that formed the study group. Data collection was performed by reviewing medical records, which were processed through SPSS to determine the relationship between variables of study; reached the following conclusions: in most patients, the clinical characteristics of labor were normal or physiological; some clinical feature of labor dystocia were dystocia uterine hypertonia and dynamic as hyper systole (22.5%); dystocia fetal presentations (15.0%); cervical dystocia (17.5%). In newborns with acute fetal distress, they had nuchal cord (27.5%); thick green liquid amniotic fluid or green (37.5%); fetal bradycardia (27.5%); plus the DIPS DIPS II and III (32.5%). Also 90.0% of infants had moderate depression minute (Apgar of 4-6); then the 67.5% achieved good recovery condition of the newborn (Apgar of 7-10) at 5 minutes. Clinical signs of acute fetal distress concomitant with some clinical characteristics of labor were expelling meconium; circular cord; dystocia fetal heart rate; newborn with severe to moderate depression. Concluding: there is no statistical relationship (p> 0.05) between clinical characteristics of labor and fetal distress in mothers treated at the Hospital II-2 MINSA Tarapoto. June - September 2014 period.